Estimates of the Neutral Rate of Interest in Norway - Leif Brubakk; Jon Ellingsen; Ørjan Robstad (Norges Bank, 2018)
In this paper, we estimate the neutral real rate for the Norwegian economy using two different empirical models, a vector autoregressive model with time-varying parameters (TVP-VAR) and a State-Space (SS) model similar to the Laubach-Williams model, respectively. In line with international evidence, all estimates indicate a falling trend. Furthermore, the estimates for Norway suggest that the Norwegian neutral short-term money market rate is now close to 0 percent in real terms.
hdl:11250/2577273
Keywords: 330